A novel flash boosted evaporation process for alumina refineries. (5th February 2016) - Rahimi, Bijan; Regenauer-Lieb, Klaus; Chua, Hui Tong; Boom, Eric; Nicoli, Silvio; Rosenberg, Steve
Graphical Abstract: A novel Flash Boosted Thermal Vapour Compression Multi Effect Evaporation (FB-TVC-MEE) process saves 26% live steam consumption as compared to conventional TVC-MEE process in a refinery application. Highlights: A novel evaporation process has been developed for mineral refineries. It can save around 82% of the selected evaporation unit's available live steam. Its thermal performance is 468% better than the current evaporation process. A capital cost analysis has shown the economic potential of this novelty. Abstract: We have developed a novel flash boosted evaporation process that utilises the available waste heat sources of the evaporation units to reduce live steam consumption for evaporation purpose in alumina refineries. The results show a significant reduction in the live steam consumption of the evaporation plant in one of the major alumina refineries in Western Australia. This system can be attached to the main evaporation process without any process interruption. In this case, the available waste stream is utilised to recover the duty of one of the selected evaporation units, and it shows that the selected unit can be completely turned off, resulting in 82% of its relevant live steam consumption being saved. A detailed capital cost analysis and pumping power consumption evaluation is presented as well. This technology is also applicable to mineral refineries in general that involves re-concentrating liquor and water balance management.